Role of constructed wetlands in mitigating the challenges of industrial growth and climate change impacts in the context of developing countries - Islam, Md. Al Sadikul; Saeed, Tanveer; Majed, Nehreen (Frontiers in Environmental Science, 2022)
One of the most persistent issues affecting individuals in developing countries is the lack of access to safe drinking water and sanitary facilities. The adoption of centralized water, energy, and cost-intensive technology has proven ineffective in addressing the complex water-related challenges that have arisen as a consequence of growing urbanization in developing nations. Constructed wetlands have emerged as an effective wastewater treatment solution with natural applications. The fundamental goal of this study is to offer a complete overview of the wide variety of practices, uses, and investigations of constructed wetlands systems for eliminating different pollutants from wastewater in developing countries leading to placing them in the context of climate change, environmental resource planning, and sustainable wastewater treatment systems. CWs offer significant levels of treatment performances with hybrid systems achieving contaminant removal efficiencies up to 93.82% for total suspended solids, 85.65% for chemical oxygen demand, and 80.11% for ammonia nitrogen which is adequate with respect to other viable alternatives. In terms of Biological Oxygen Demand (BOD5), the highest elimination (84.06%) was achieved in hybrid systems when compared to Free water surface CWs (65.34%), Horizontal sub-surface CWs (75.1%), and Floating treatment wetland (55.29%). The maximum power density generation through the microbial fuel cell-based constructed wetlands ranges between 50 and 86 mW/m2 in Bangladesh (integrated tidal flow) and 852 mW/m3 in China (vertical flow), and the production of bioenergy has been evidenced up to 1,836.5 GJ/hector/year. Annually, wastewater treatment plant systems (WTPs) generate around a hundred times more Methane (CH4), Nitrous oxide (N2O), and carbon dioxide (CO2) than CWs. In metropolitan cities, WTPs may lead to a considerable increase in upstream land use, which could be minimized by promoting CWs in these areas. The potential utility of different CWs in protecting and preserving estuarine quality within the present regulatory framework is finally addressed in the study, emphasizing that it can balance the impacts of industrial expansions in developing countries for subsequent mitigation and adaptation to climate change.